Distinct high molecular weight organic compound (HMW-OC) types in aerosol particles collected at a coastal urban site. (December 2017) - Dall'Osto, M.; Healy, R.M.; Wenger, J.C.; O'Dowd, C.; Ovadnevaite, J.; Ceburnis, D.; Harrison, Roy M.; Beddows, D.C.S.
Abstract: Organic oligomers were discovered in laboratory-generated atmospheric aerosol over a decade ago. However, evidence for the presence of oligomers in ambient aerosols is scarce and mechanisms for their formation have yet to be fully elucidated. In this work, three unique aerosol particle types internally mixed with High molecular weight organic compounds (HMW-OC) species - likely oligomers - were detected in ambient air using single particle Aerosol Time-Of-Flight Mass Spectrometry (ATOFMS) in Cork (Ireland) during winter 2009. These particle types can be described as follows: (1) HMW-OCs rich in organic nitrogen - possibly containing nitrocatechols and nitroguaiacols - originating from primary emissions of biomass burning particles during evening times; (2) HMW-OCs internally mixed with nitric acid, occurring in stagnant conditions during night time; and (3) HMW-OCs internally mixed with sea salt, likely formed via photochemical reactions during day time. The study exemplifies the power of methodologies capable of monitoring the simultaneous formation of organic and inorganic particle-phase reaction products. Primary emissions and atmospheric aging of different types of HMW-OC contributes to aerosol with a range of acidity, hygroscopic and optical properties, which can have different impacts on climate and health. Highlights: Single particle mass spectra are collected at an urban coastal site. Three different types of HMW-OC are characterized. A unique HMW-OC type internally mixed with sea salt is found.